First laboratory study of air-sea gas exchange at hurricane wind speeds - Krall, Kerstin Ellen; Jähne, Bernd (Ocean science, 2014)
Abstract. In a pilot study conducted in October and November 2011, air-sea gas transfer velocities of the two sparingly soluble trace gases hexafluorobenzene and 1,4-difluorobenzene were measured in the unique high-speed wind-wave tank at Kyoto University, Japan. This air-sea interaction facility is capable of producing hurricane strength wind speeds of up to u10=67 m s-1. This constitutes the first lab study of gas transfer at such high wind speeds. The measured transfer velocities k600 spanned two orders of magnitude, lying between 11 cm h-1 and 1180 cm h-1with the latter being the highest ever measured wind-induced gas transfer velocity. The measured gas transfer velocities are in agreement with the only available data set at hurricane wind speeds (McNeil and D'Asaro, 2007). The disproportionately large increase of the transfer velocities found at highest wind speeds indicates a new regime of air-sea gas transfer, which is characterized by strong wave breaking, enhanced turbulence and bubble cloud entrainment.